2022
DOI: 10.3390/jof8020114
|View full text |Cite
|
Sign up to set email alerts
|

Basal Parasitic Fungi in Marine Food Webs—A Mystery Yet to Unravel

Abstract: Although aquatic and parasitic fungi have been well known for more than 100 years, they have only recently received increased awareness due to their key roles in microbial food webs and biogeochemical cycles. There is growing evidence indicating that fungi inhabit a wide range of marine habitats, from the deep sea all the way to surface waters, and recent advances in molecular tools, in particular metagenome approaches, reveal that their diversity is much greater and their ecological roles more important than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 170 publications
0
7
0
Order By: Relevance
“…Interactions between phytoplankton and parasitic fungi influence the health and dynamics of phytoplankton populations directly, through parasitism, and indirectly by impacting the flow of organic matter within and among microbial communities (Grossart et al., 2019; Sime‐Ngando, 2012; Van den Wyngaert et al., 2022). Despite their ecological importance, parasitic, microalgae‐associated marine fungi remain understudied in comparison to other microbial groups, especially with regard to implications for ocean biogeochemistry (Ilicic & Grossart, 2022).…”
Section: Biogeochemical Impacts Of Planktonic Marine Fungimentioning
confidence: 99%
“…Interactions between phytoplankton and parasitic fungi influence the health and dynamics of phytoplankton populations directly, through parasitism, and indirectly by impacting the flow of organic matter within and among microbial communities (Grossart et al., 2019; Sime‐Ngando, 2012; Van den Wyngaert et al., 2022). Despite their ecological importance, parasitic, microalgae‐associated marine fungi remain understudied in comparison to other microbial groups, especially with regard to implications for ocean biogeochemistry (Ilicic & Grossart, 2022).…”
Section: Biogeochemical Impacts Of Planktonic Marine Fungimentioning
confidence: 99%
“…Recently studies also revealed that fungi take part in organic matter metabolism in marine environments (Baltar et al, 2021;Ilicic & Grossart, 2022). However, the role of global microbial consortia in this process remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…In aquatic environments, especially marine, prokaryotes are commonly associated with terrestrial organic matter degradation, due to their broad environmental adaptability and versatile metabolic pathways (Li et al., 2020; Li, Dong, et al., 2022; Wang et al., 2021; Yu et al., 2018). Recently studies also revealed that fungi take part in organic matter metabolism in marine environments (Baltar et al., 2021; Ilicic & Grossart, 2022). However, the role of global microbial consortia in this process remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…2019 ), so for an in-depth understanding of diatom communities it is vital to elucidate the diversity and interactions of oomycetes with their diatom hosts ( Scholz et al . 2016 , Illicic & Grossart 2022 ). While previously almost all diatom parasitoids had been attributed to a single genus, Ectrogella ( Dick 2001 ), recent research has shown that diatom parasitism has evolved multiple times and that species parasitising diatoms can be found throughout the oomycete tree of life ( Buaya & Thines 2020c ).…”
Section: Introductionmentioning
confidence: 99%